Animal Cognition in an Urbanised World - Lee, Victoria E.; Thornton, Alex (Frontiers in Ecology and Evolution, 2021)
Explaining how animals respond to an increasingly urbanised world is a major challenge for evolutionary biologists. Urban environments often present animals with novel problems that differ from those encountered in their evolutionary past. To navigate these rapidly changing habitats successfully, animals may need to adjust their behaviour flexibly over relatively short timescales. These behavioural changes, in turn, may be facilitated by an ability to acquire, store and process information from the environment. The question of how cognitive abilities allow animals to avoid threats and exploit resources (or constrain their ability to do so) is attracting increasing research interest, with a growing number of studies investigating cognitive and behavioural differences between urban-dwelling animals and their non-urban counterparts. In this review we consider why such differences might arise, focusing on the informational challenges faced by animals living in urban environments, and how different cognitive abilities can assist in overcoming these challenges. We focus largely on birds, as avian taxa have been the subject of most research to date, but discuss work in other species where relevant. We also address the potential consequences of cognitive variation at the individual and species level. For instance, do urban environments select for, or influence the development of, particular cognitive abilities? Are individuals or species with particular cognitive phenotypes more likely to become established in urban habitats? How do other factors, such as social behaviour and individual personality, interact with cognition to influence behaviour in urban environments? The aim of this review is to synthesise current knowledge and identify key avenues for future research, in order to improve our understanding of the ecological and evolutionary consequences of urbanisation.